Including Assets-Based Mitigation in Sentencing - Vartkessian, Elizabeth S. (Criminal justice policy review, 2020)
Mitigation evidence consists of information about an accused person that is typically used to advocate for a less severe sentence. Such evidence most frequently consists of information related to the crime and personal factors that can be separated into two broad categories: deficits and assets-based mitigation. This article focuses on the importance of assets-based mitigation in sentencing and evaluates if and how state sentencing procedures contemplate and allow for consideration of such evidence. A content analysis of available state sentencing procedures reveals that states tend to circumscribe mitigation to factors related to the crime or deficits, but largely neglect to give a vehicle to consider assets-based mitigation, which should play a central role in achieving just outcomes. This article therefore argues for reform to sentencing laws to better accommodate assets-based mitigation by including information related to the defendant’s capacity for growth, self-improvement, and redemption.